A Study on the Contribution of Fdi to Economic Growth: Exploring the Impact of Foreign Direct Investment on Economic Growth (Journal of Advances and Scholarly Researches in Allied Education, 2014)
FDI may be defined as an investment involvinga lasting interest and control by an investor who is a resident of anothereconomy, other than that of the host economy. In the simple sense, FDI impliedthat the investor has a significant degree of influence on the management.Foreign Direct Investments are investments made by residents of one economywith the objective of establishing a lasting interest in a company located inanother economy (host economy).